Direct and Indirect Protection with Pediatric Quadrivalent Live-Attenuated Influenza Vaccination in Europe Estimated by a Dynamic Transmission Model - Laetitia Gerlier; Judith Hackett; Richard Lawson; Sofia Dos Santos Mendes; Catherine Weil-Olivier; Markus Schwehm; Martin Eichner (Journal of Health Economics and Outcomes Research)
# Objectives To estimate the public health impact of annual vaccination of children with a quadrivalent live-attenuated influenza vaccine (QLAIV) across Europe.